2013
DOI: 10.1017/sjp.2013.22
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Service Science Teachers’ Teaching Self-Efficacy in Relation to Personality Traits and Academic Self-Regulation

Abstract: Abstract. The aim of this study is to examine the relationship among pre-service science teachers' personality traits, academic self-regulation and teaching self-efficacy by proposing and testing a conceptual model. For the specified purpose, 1794 pre-service science teachers participated in the study. The Teachers' Sense of Efficacy Scale, the NEO Five-Factor Inventory, and the Motivated Strategies for Learning Questionnaire were administered to assess pre-service science teachers' teaching self-efficacy, per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 55 publications
4
22
2
Order By: Relevance
“…Data collection is one of the important phases that direct researchers towards ending research process administering self-constructed / standardized instrument. Research collected data from teachers by administering standardized long form Tschannen-Moran and Hoy (2001) long form self-efficacy scale; known as Ohio State Teachers' Efficacy Scale (Senler & Sungur-Vural, 2013). Researcher sought unfettered and unrestricted permission from authors upon request for scale usage.…”
Section: Data Collection Instrumentation and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Data collection is one of the important phases that direct researchers towards ending research process administering self-constructed / standardized instrument. Research collected data from teachers by administering standardized long form Tschannen-Moran and Hoy (2001) long form self-efficacy scale; known as Ohio State Teachers' Efficacy Scale (Senler & Sungur-Vural, 2013). Researcher sought unfettered and unrestricted permission from authors upon request for scale usage.…”
Section: Data Collection Instrumentation and Proceduresmentioning
confidence: 99%
“…Normality of the data was confirmed by calculating Shapiro-Wilk's test in SPSS, p>.05, n<2000. Normal distributed data are considered as more trendy, easy to exercise, provide excellent estimation, grant perfect direction towards application of parametric and non-parametric test, easy to analyze and interpret for smooth results (Elliott & Woodward, 2007;Öztuna, Elhan, & Tüccar, 2006;Senler & Sungur-Vural, 2013;Thode, 2002). Literature reported that Shapiro-Wilk's test having value, p>.05, n<2000 and Kolmogrov-Smirnov test, p>.05, n<2000 are appropriate tests that confirm normality of data (Elliott & Woodward, 2007;Field, 2009;Peat & Barton, 2008;Singh, Masuku, 2014).…”
Section: Data Collection Instrumentation and Proceduresmentioning
confidence: 99%
“…In fact, there is some research on this issue (for e.g. Senler & Sungur, 2013). As mentioned before; however, these pre-service teachers' beliefs about malleability of their traits and abilities with effort imply that they may be successful in their future career.…”
Section: Discussionmentioning
confidence: 96%
“…According to Senler and Sungur-Vural (2013) and Xiao and Wilkins (2015), academics' personality traits in higher education can usually be measured by the big five personality traits. The big five personality traits described by Costa and McCrae (1992), Tupes and Christal (1992), Lounsbury et al (2007), Salleh et al (2014), DeYoung (2015), and DeYoung et al (2016 include the following: neuroticism, which is the opposite of emotional stability and reflects academics' emotional reaction when they experience something positive or negative; extraversion, which describes academics who may tend to be sociable and strive to achieve high performance; openness, an attribute that shows an active imagination and independence; agreeableness, which describes academics who are characterised by trust, altruism, reputation, or modesty; and conscientiousness, which describes academics who are fair, reliable, systematic, or dutiful.…”
Section: Methods Research Hypothesesmentioning
confidence: 99%